The debt situation in four South American countries: a comparison of Argentina, Brazil, Chile and Uruguay - Sangmeister, Hartmut (Economics, 1992)
The data available suggest that, in the 1990s again, Argentina, Brazil and Chile, and probably Uruguay, will only be able to pay the liabilities on their existing loans with the aid of fresh money. If their debt service is not substantially reduced first, the Latin American debtor countries will not have the time they need for the required extensive structural adjustment programmes to show any sign of success
Keywords: Argentinien; Chile; Brasilien; Uruguay; Aufsatz in Zeitschrift